The Effectiveness of Internal Control System and Role of Internal Audit on Local Government Performance - Marita Kusuma Wardani (Journal of International Conference Proceedings (JICP), 2019)
This study aims to analyze the effectiveness of control environmental components and monitoring activities as part of the internal control system and examine the effect of partially control environment variables, monitoring activities and the role of internal audit on the performance of local governments in Surakarta. The samples used were 126 employees consisting of a head and a staff in 33 regional organization in Surakarta. The method of analysis using descriptive statistics and linear regression. The results showed that the components of the control environment and monitoring activity on the local government in Surakarta has been done effectively. Research also proves their influence in partial control environment, monitoring activities and the role of internal audit on local government performance.